Analisis Praktik Jual Beli Online pada Shopee dalam Perspektif Ekonomi Syariah: Studi Ulasan Pengguna terhadap Unsur Gharar,Maysir,Tadlis - Muhammad Aghna Dhafin Kurniawan; Moh.Mukhsin (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to analyze buying and selling transaction practices on shopee e-commerce platform from the perspective of Islamic economic law. Along with the rapid digitalization of the economy, various challenges have emerged regarding ethics and transparency in virtual transactions, such as the presence of gharar (uncertainty), maysir (speculation), and tadlis (fraud), which can be detrimental to consumers. This research employs a [e.g., descriptive qualitative] method with a qualitative descriptive approach. Data were collected through literature review and analysis of user reviews. The results indicate that although e-commerce offers efficiency, there are still practices that are not fully in line with Sharia principles, particularly regarding product information transparency and certain payment system mechanisms. This research emphasizes the importance of strengthening the implementation of Islamic business ethics, specifically the principles of transparency and trustworthiness, to ensure the well-being of all parties involved in transactions. The recommendations of this study include the need for enhanced platform oversight of product descriptions and the importance of digital literacy for consumers to be more diligent in reviewing product feedback. These findings are expected to serve as a reference for developing a more inclusive digital economic ecosystem that aligns with Sharia economic principles in the future.